Micro classes in teacher training processes (Memorias Sifored - Encuentros Educación UAN, 2021)
Promote learning processes in context for teacher training from assuming the professional role making use of planning, design and socialization of micro classes and their evaluation from rubrics
Keywords: microclassroom; evaluation; teacher training